A triplicated wheat-rye chromosome segment including several 12-OXOPHYTODIENOATE REDUCTASE III genes influences magnesium partitioning and impacts wheat performance at low magnesium supply - Gualano, Leonardo D.; Moriconi, Jorge I.; Gabay, Gilad; Tranquilli, Gabriela; Pacheco, Pablo H.; Dubcovsky, Jorge; Santa-María, Guillermo E. (Elsevier, 2024)
We previously reported a structural rearrangement between wheat (Triticum aestivum) and rye (Secale c ereale) chromosomes 1BS/1RS that increased the dosage of 12-OXOPHYTODIENOATE REDUCTASE III (OPRIII) genes involved in jasmonate biosynthesis (henceforth, 1RW line), and that drastically reduced primary root growth relative to a control line with the intact 1RS chromosome (henceforth, 1RS). In this study, we show that the increased gene-dosage of this region is associated with increases in the shoot-root partitioning of magnesium (Mg). Moreover, both a CRISPR-edited 1RW line with reduced OPRIII dosage and the 1RW line treated with the jasmonate biosynthesis inhibitor ibuprofen showed reduced differences in shoot-root Mg partitioning than 1RW. The observed differences in Mg partitioning between 1RS and 1RW plants occur over a wide range of external Mg supplies and imply opposite trends of Mg accumulation in roots and shoots. Furthermore, we show an association between the increase of shoot-root Mg partitioning and increased tolerance of the 1RW line to low levels of Mg supply. In summary, our results provide evidence of the role of the jasmonate pathway on the dynamics of Mg accumulation in roots and shoots, which correlates with the performance of wheat plants under conditions of Mg scarcity.